Importance of resolving fungal nomenclature: The case of multiple pathogenic species in the Cryptococcus genus - Ferry Hagen (2018)
© 2017 Hagen et al. Cryptococcosis is a major fungal disease caused by members of the Cryptococcus gattii and Cryptococcus neoformans species complexes. After more than 15 years of molecular genetic and phenotypic studies and much debate, a proposal for a taxonomic revision was made. The two varieties within C. neoformans were raised to species level, and the same was done for five genotypes within C. gattii. In a recent perspective (K. J. Kwon-Chung et al., mSphere 2:e00357-16, 2017, https://doi .org/10.1128/mSphere.00357-16), it was argued that this taxonomic proposal was premature and without consensus in the community. Although the authors of the perspective recognized the existence of genetic diversity, they preferred the use of the informal nomenclature "C. neoformans species complex" and "C. gattii species complex." Here we highlight the advantage of recognizing these seven species, as ignoring these species will impede deciphering further biologically and clinically relevant differences between them, which may in turn delay future clinical advances.